(untitled) (FULafia Journal of Science and Technology, 2023)
Plants have been known to be used in the treatment and management of diseases, and this is due to the presence of phytochemicals. Thus, the screening of plants, both quantitatively and qualitatively, has got the interest of researchers. Moringa oleifera and Vernonia amygdalina are two plants that have very rich application in trado-medicine for various purposes. Thus this study seeks to understand the phytochemical profile when both plants are mixed. Ethanol, lime and aqueous extracts were used, of which lime extract gave the highest percentage yield of 27.3%, while ethanol and aqueous extracts gave 13.6% and 11.2% respectively. The qualitative phytochemical screening showed that only phenols and tannins were detected in all the three extracts.Flavonoids were only detected in the aqueous extract and alkaloids detected in the ethanolic extract only. The quantitative analysis showed the presence of all the five phytochemical classes in all extracts with the lime extract having the lowest values for all phytochemical classes tested for. The aqueous extract showed a generally good concentration in all five phytochemicals. Saponins, tannins and flavonoids were highest in the aqueous extract of 13.2%, 49.32 mg/mL and 2.10mg/mL respectively. Phenols and alkaloids were highest in the ethanolic extract of 5.48 G.A. Eq. mg/mL and 3.2% respectively. This result showed that the mixture of Moringaoleifera and Vernoniaamygdalina is a good dietary combination